PALELINTANGAN DALAM SENI RUPA POP - Sudana, I Made; Setem, I Wayan; Mudana, I Wayan (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
Balinese traditional painting, especially Wayang Kamasan painting, has a long and rich history. However, in the era of globalization and modernization, traditional arts often experience difficulties in surviving. This phenomenon is not unique to Bali, but is happening in traditional art communities around the world. With the advent of digital media, fast-paced urban lifestyles, and changing cultural values, traditional artists often feel pressure to adapt their work to changing market tastes. Some Balinese traditional artists are trying to incorporate modern elements into their work to appeal to the younger generation and the international market, as well as to preserve the culture. Nevertheless, this challenge cannot be ignored and maintain the sustainability of this traditional painting art in the face of increasing modernization trends. This creation discusses the creation of pop art by displaying the form of palelintangan which is poured into several mass cultural products in order to form creative and innovative works. In its creation process, this work follows the principles outlined by Hawkins in his book